Person Pronoun Deixis in Indonesian Cellular Operators Advertisements: Represent the Participants? - Novitasari, Ningrum; Mutmainnah, Yulia; Nugraheni, Yunita (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
This qualitative descriptive research uses non participatory observation method with Telkomsel and Indosat cellular operator advertisements as the objects. There are three types of person pronoun deixis: first, second and third person pronoun deixis which are consist of 14 deixis, namely: ku, aku, aku, gue, kita, kami, mu, kamu, kamu, loe, kamu, bang, dia, dan mereka. The most commonly person pronoun deixis used in Telkomsel and Indosat advertisements is "aku". In addition, it was found that the person pronoun deixis in the Telkomsel advertisement varied more than it is in Indosat advertisements. The use of each personal pronoun deixis depends on the close of participants, situation (formal or less formal), and who the participant itself.